A study of the income distribution and inequality among residents of Batang Sadong, Samarahan Division, Sarawak, in 2007 - Puasa, Ahmad Fauzi; Husaini, Sulaiman; Mohamad Muslim, Huda Farhana (2007)
The Gini coefficient is one of the socio-economic tools used in measuring inequality of income distribution. The Gini coefficient is defined as a ratio with value between 0 and 1, with 0 corresponding to perfect income equality, which means everyone has the same income, and 1 corresponding to perfect income inequality, which means that one person has all the income, while everyone else has zero income. This paper attempts to study the income distribution for Batang Sadong, Samarahan Division, using census data collected by the Samarahan Division Office in 2007. The data show that the monthly household income for the farmers in Batang Sadong ranges from RM40 per month to RM3,550 per month. The average monthly income is estimated at about RM361.11 per month, which is below the hardcore poverty level of RM482 per month for Sarawak. The Gini coefficient for Batang Sadong has the overall value of 0.3161 and ranges from 0.18748 to 0.41354. This study has proven that the income gap between the rich and the poor for Batang Sadong is not large. However, as the average household income is very low, this area requires an intensive development program to improve the standard of living of the residents.